A impressão do consenso : uma análise político-epistemológica do SARESP na Folha de S. Paulo e no Jornal da APEOESP - Farias, Jaime (2015)
The research is based on the statements circulating in the political/media relationship, from which reviews the statements related to the school performance evaluation system of São Paulo state (SARESP). For this, texts were selected from two newspapers of different natures, published between 1995, beginning of Mario Covas government, which implemented the SARESP and 2010, the last year of the government of José Serra. Folha de S. Paulo characterized as a daily newspaper, commercial, nationwide, whose activities are based on the business logic, articulated the demands of an industrial line news production. Jorrnal da APEOESP is an information vehicle of the union of official school teachers of the São Paulo state (APEOESP), with circulation addressed to the shareholders, free distribution and variable frequency, whose journalistic practices are linked to the conflicts underlying the defense of the rights of the teaching category. SARESP is an external evaluation tool of the São Paulo state‘s school system, established in 1996. It consists of an examination applied to all students in certain grades, being compulsory in state public schools and membership in municipal public schools and private networks. As a theoretical basis for the analysis of texts from newspapers, stand out Foucault's notions of power, statement, discourse and regime of truth. The study aimed to identify, in the political/media relationship, certain statements considered “true”, related to SARESP. It was sought to identify aspects of media practice to indicate the formation of a “performative discourse”, due to the appreciation of criteria of efficiency and innovation, related to the neoliberal policy reform process. The study of the participation of the press in the circulation of “performative discourse” allowed to establish an “impression of consensus” about the SARESP. Although the effects of this process have worked towards interdict other possible discourses, it was noticed that there were some statements that came constitute a "discourse of resistance" related to criticism of performativity's criterias. It is concluded, in this regard, that the statements related to improving the quality of education is interconnected to the statements dealing SARESP as the legitimate measure of quality, featuring the preponderance of “performativity of speech”, however, associated and constant relationship with different settings of “discourse of resistance”.